Analisa Performansi Komunikasi Lora (Long Range) pada Sistem Monitoring Buoy di Laut - Sa'adah, Nihayatus; Aries Pratiarso; Faridatun Nadziroh; Nailul Muna; Karimatun Nisa’; I Gede Puja Astawa; Tri Budi Santoso; Sultan Syahputra Yulianto (AI Society & STMIK Indonesia, 2024)
LoRa (Long Range) is a leading technology in Low Power Wide Area Networks (LPWAN), ideal for Internet of Things (IoT) applications. Designed for long-range communication with low power consumption, LoRa is used in monitoring navigation buoys, critical aids in marine waters. An IoT-based monitoring system is essential for maintaining buoy functionality. LoRaWAN, with a range of 15 kilometers under line of sight (LoS) conditions, is employed for IoT connectivity in this system. In this study, 915 MHz LoRa communication was used in buoy monitoring, with performance evaluated based on signal-to-noise ratio (SNR) and received signal strength indicator (RSSI). Measurements showed an average RSSI greater than -120 dB and an average SNR greater than -20 dB, indicating LoRa's suitability as a communication network for buoy monitoring systems.